Person and Being: Conversation with T.F. Torrance about the Monarchy of God. (21st June 2012) - Dean, Benjamin
Abstract In whom is the unified rule of God centred? Does ultimate determination and authority reside with God the Father or is supreme power shared equally by the Father, Son and Holy Spirit? T.F. Torrance's conception of a triune Monarchy, with its differentiated senses of God's Fatherhood, is here expounded and contrasted with Karl Barth's account of command and obedience as integral to God's eternal Being. A brief exegetical study in the Fourth Gospel is also undertaken to seek clarification. The main strengths of Torrance's view are reckoned the unqualified divinity of the Son and Spirit, and their full participation together with the Father in all God's ways and works. A weakness is identified, however, in an under‐determination of the Father's fatherliness. Resolution is then pursued in terms of Person and Being. Although Torrance makes wide‐ranging use of these terms, he does not appear to employ them sufficiently regarding the Monarchy. It is subsequently argued that with respect to Person God the Father is Monarch, while with respect to Being the Three share the Monarchy of God equally and eternally.